The integration of an effective disaster risk reduction system in Namibia based on vulnerabilities of stakeholders in the Zambezi region - Kanyimba, Alex T.; Siyambango, Nguza (Journal for Studies in Humanities and Social Sciences, 2014)
Namibia has structures in place for disaster risk reduction. However, the need to mainstream the disaster risk reduction policy at all levels has been emphasised in the literature. The aim of this article is to present opportunities for the integration of effective disaster risk reduction in Namibia based on vulnerabilities of stakeholders in the Zambezi region. The data was collected by quantitative and visual research methods. The quantitative data was evaluated by means of the statistical package for social sciences and the visual data by semiotic analysis. In the opinion of members of civil society, the community and local government agencies, flooding is on the increase and losses in assets have been experienced. The Namibian disaster reduction system consequently faces a challenge. This study recommends an approach that is holistic, society that can act together in reducing disaster risks and facilitate community coalitions